Realistic and Efficient Rendering of Free-form Knitwear - Zhong, Hua; Xu, Ying-Qing; Guo, Baining; Shum, Harry (2000)
We present a method for rendering knitwear on free-form surfaces. Starting from a parametric surface, a stitch pattern, and optionally a color pattern, we can produce highly realistic rendering of knitwear efficiently. Our method draws its realism from two sources. First, we have developed a novel and sophisticated model for free-form knitwear that takes into consideration the interactions between neighboring loops and subtle irregularities in the position of the loops. Second, we have derived a method for rendering yarn microstructure with user control of the fluffiness of the yarn. The efficiency of our method comes from the fact that it displays free-form knitwear as Gouraud-shaded polygons, which current graphics hardware is optimized to draw. In contrast, previous techniques for rendering free-form knitwear requires tracing curved rays and therefore cannot benefit from mass-market graphics hardware.